Study of Iron Supplementation on Rice Genotypes - Saini, R.; Dahiya, A.; Saini, H. S.; Brar, B.; Verma, S.; Verma, A. (International Journal of Bio-resource and Stress Management, 2022)
Promising rice genotypes were evaluated during June to October in the Department of Chemistry and Biochemistry, CCS HAU, Hisar, Haryana, for 2015−2016 and 2016−2017 cropping seasons. Biochemical changes in root tissues were estimated in response to augmentation of iron concentrations during vegetative to reproductive stages. Estimated values of metabolities observed variation in ascorbic acid from 343.3−680.2 among treatments for this study. Values of hydrogen per oxide expressed deviation from 506.8−230.8, while malondialdehyde deviated from 10.9−30.8. Very large deviation had expressed by peroxidase values i.e. 38.1−160.8. Larger values expressed by hydrogen per oxide as varied from 187.3−457.5, and least total deviation from 9.9−24.2 for malondialdehyde values. The first principal component accounted for 73.8% of the total variation among estimated values and larger contribution expressed by peroxidase, catalase, superoxide dismutase of vegetative stage and superoxide dismutase, catalase, ascorbate peroxidase of reproductive stage etc. Total of 22.6% to the total variation contributed by second principal component with major contributors were malondialdehyde, hydrogen peroxide, superoxide radicals of vegetative stages along with malondialdehyde, hydrogen peroxide, superoxide radicals, of reproductive stages. Agronomic biofortification with a proper balance of iron augmentation induce desirable effect on the physiological process of the plants.